Vaporware, Suddenware, and Trueware: New Product Preannouncements Under Market Uncertainty - Ofek, Elie; Turut, Özge (Marketing Science, 2013)
A firm may want to preannounce its plans to develop a new product in order to stimulate future demand. But given that such communications can affect rivals' incentives to develop the same new product, a firm may decide to preannounce untruthfully in order to deter competitors. We examine an incumbent's preannouncement strategy when there is uncertainty regarding the commercial viability of a new product opportunity and a threat of rival entry. Each firm has a private assessment of the market potential for the new product. Two competitive incentives arise for the incumbent in terms of discouraging rival entry: it can use preemptive communication or it can remain silent and instill a pessimistic market potential outlook. We find that an incumbent prefers to follow a vaporware strategy—i.e., declares plans to pursue a new product opportunity even when it may have no development intentions—when its market forecasting capabilities are weak and the demand-side benefits from preannouncing are small. By contrast, when the incumbent has strong market forecasting capabilities and the demand-side benefits are small, the incumbent adopts a suddenware strategy—i.e., remains silent about its new product plans even when it actually plans to develop the new product. Finally, when its market forecasting capabilities are strong and the demand-side benefits are large, the incumbent prefers to engage in a trueware strategy—i.e., truthfully preannounces development plans. We show that an interplay between competition-related and demand-related considerations is what allows trueware to emerge as an equilibrium in the absence of any ex post cost to engaging in vaporware. In an extension, we let the incumbent's actual development plans leak out and allow the entrant to wait and learn those plans prior to setting a research and development level. We identify conditions for the entrant to postpone development despite the risk of being late to market, as well as conditions for the entrant to commence development immediately despite not knowing the incumbent's plans based on the observed preannouncement strategy.